MENINGKATKAN KEMAMPUAN MOTORIK HALUS DENGAN METODE DEMONSTRASI DI RA ANNUR BARUGA KENDARI - Ety Nur Inah (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2017)
AbstarctThis study aims to improve the children’s fine motor skills through sewing activities with demonstration methods on B2 group at RA An-Nur Baruga of Kendari. This research is a Classroom Action Research (CAR) conducted in two cycles. Subjects in this study were the children of B2 group at RA An-Nur Baruga which consisted of 11 children; 7 boys and 4 girls. Based on the observation, it showed that the children’s sewing ability could improve their motor skills through demonstration methods. After doing the action cycle I, eight children were able to show good to very good development. However, the completeness percentage was not as the researcher expected. It only reached 73%. Therefore, the researcher applied cycle II treatment. In cycle II, the children showed progress that ten of eleven students showed very good development of their fine motor skill. The completeness percentage reached to 91% which even exceeded the predetermined indicator of 75%. The percentage of success before the action until the second cycle is 55%.